Nonisocyanate based polyurethane/silica nanocomposites and their coating performance - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (SPRINGER, 2008)
A series of silica nano-particles with different size were prepared by sol-gel technique, then surface modification by using cyclic carbonate functional organoalkoxysilane (CPS) was performed. Various amounts of carbonated silica particles directly added into carbonated soybean oil (CSBO) and carbonated polypropylene glycol (CPPG) resin mixture to prepare polyurethane-silica nanocomposite coating compositions by nonisocyanate route using an aliphatic diamine as a curing agent. Cupping, gloss, impact, and taber abrasion tests were performed on aluminum panels coated with those nano-composite formulations and tensile tests, thermogravimetric and SEM analyses were conducted on the free films prepared from the same coating formulations. An increase in abrasion resistance of CSBO-CPPG resin combination with the addition of silica was observed. In addition, the maximum weight loss of CSBO-CPPG resin combination was shifted to higher temperatures with incorporation of silica nano-particles The positive effect of modified silica particles on thermal stability of CSBO-CPPG system could be explained in such a way that PPG chains are able to disperse particles in the medium throughout the interactions between ether linkages and silanol groups.
Keywords: silica; nonisocyanate polyurethane; nanocomposite; cyclic carbonate; CARBONATE FUNCTIONAL POLYMERS; CYCLIC CARBONATE; SOYBEAN OIL; DIOXIDE; SILICA; SIZE; EPOXIDE; GROWTH